2002
DOI: 10.1103/physreve.66.051104
|View full text |Cite
|
Sign up to set email alerts
|

Crossover effects in a discrete deposition model with Kardar-Parisi-Zhang scaling

Abstract: We simulated a growth model in (1+1) dimensions in which particles are aggregated according to the rules of ballistic deposition with probability p or according to the rules of random deposition with surface relaxation (Family model) with probability 1-p. For any p>0, this system is in the Kardar-Parisi-Zhang (KPZ) universality class, but it presents a slow crossover from the Edwards-Wilkinson class (EW) for small p. From the scaling of the growth velocity, the parameter p is connected to the coefficient lambd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
(56 reference statements)
1
39
1
Order By: Relevance
“…In other models with crossover between different growth dynamics, it is observed that matching the scaling relations for the roughness of both dynamics leads to correct predictions of t c [9,12]. Following this reasoning, the W values in Eqs.…”
Section: Scaling Of Surface Roughnessmentioning
confidence: 75%
“…In other models with crossover between different growth dynamics, it is observed that matching the scaling relations for the roughness of both dynamics leads to correct predictions of t c [9,12]. Following this reasoning, the W values in Eqs.…”
Section: Scaling Of Surface Roughnessmentioning
confidence: 75%
“…Likewise, large scales are essential in simulation studies of roughening in the two-component growth models that combine one process governed by linear EW dynamics with another process governed by nonlinear KPZ dynamics [24]. Recently, Chame and Reis [25] simulated in (1+1) dimension a mixed growth where particles aggregated either by ballistic deposition (with probability p) or by random deposition with surface relaxation (with probability 1 − p). They show that for small p and sufficiently large L, the interface width has three well-defined evolution stages.…”
Section: Introductionmentioning
confidence: 99%
“…This is fundamentally different in more complex systems where the initial regime can extend over very large times [12,13,14,15,16,17,18,19,20,21,22,23,25]. As already mentioned, the Family-Vicsek scaling relation (3) assigns a new set of coordinates to the second crossover point.…”
mentioning
confidence: 99%
“…[12,13,14,15,16,17,18,19,20,21,22,23]. In a competitive growth model one considers a mixture of two different deposition processes where one of them takes place with probability p whereas the other takes place with probability 1−p.…”
mentioning
confidence: 99%